Cytotoxicity Test of Methanol Extract of Belajang Susu (Scindapsus pictus Hassk.) Against MCF-7 Breast Cancer Cells - Pince Salempa; Muharram Muharram; Oslan Jumadi; Diana Eka Pratiwi; Musniati Azis; Nurul Amaliah (Indonesian Journal of Fundamental Sciences, 2022)
Abstract. Belajang Susu Plant (Scindapsus pictus Hassk.) is a species of the genus Scindapsus including the Araceae family which has been traditionally used by the Mambi people for medicine. Plants from the genus Scindapsus contain active compounds such as calcium oxalate, flavonoids sulfate and a mixture of flavones and flavonols sulfate which can be used as anti-inflammatory, analgesic, antioxidant, anticancer and anti-tumor. This study aims to determine the potential of methanol extract of Scindapsus pictus Hassk. as an anticancer. Extraction was carried out by maceration with methanol and then tested for cytotoxicity against MCF-7 cancer cells. The results showed that the methanol extract of Scindapsus pictus Hassk. was very active against MCF-7 breast cancer cells with an IC50 value of 3.9861 μg / mL. Keywords: Belajang susu,  Scindapsus pictus Hassk., MCF-7The first section in your paper